(untitled) (Revista Kriterion, 2023)
This paper aims to map the different theoretical options related to the Precautionary Principle (PP). Great part of the literature on it can be systematized by answering to three different questions: is there a basic structure in the PP? If so, in which interpretation of the PP does this structure express itself? Finally, are its damage or knowledge conditions fixed or adjustable? The first question separates realist from non-realist approaches. The second question allows us to discriminate monist, dualist, or pluralist positions in relation to the three interpretations of the PP: decision rule, procedural requirement, or epistemic rule. Finally, the third question distinguishes rigid from non-rigid formulations of the principle. Based on this mapping, one can not only navigate through the different formulations of the PP present both in official documents and in specialized literature, but also deflect some of its common objections, and understand Hans Jonas’ eventual connection with PP. Notwithstanding, this mapping does not capture other important themes attached to PP, which motivates a final distinction between narrow and broader forms of PP.